Analysis of the Function of Regional Apparatus to Realize Strong Food Reserves in the Era of Regional Autonomy - Mohamad Hidayat Muhtar; Viorizza Suciani Putri; Farida Tuharea; Irsan (IHSA Institute, 2022)
Food Reserves and food security are two concepts that cannot be separated because good and strong food security will have implications for both national and regional food reserves. This study aims to discuss (1) the function and role of regional apparatus organizations in the era of regional autonomy? and (2) What are the problems faced in implementing Regional Food Reserves? The research method is carried out with a normative juridical type through a statute approach. The study results show that (1) The duties and functions of regional organizations in terms of food security and reserves must be integrated with local and village governments. (2) Problems in the Implementation of Regional Food Reserves, namely the Management of food security or food availability at the national and regional levels and the conversion of agricultural land, which has a tremendous impact on food reserves.